Bacterial Communities Associated With Spherical Nostoc Macrocolonies - Aguilar, Pablo; Dorador, Cristina; Vila, Irma; Sommaruga, Ruben (Frontiers in Microbiology, 2019)
Species of the genus Nostoc (Cyanobacteria) can form large colonies of up to several centimetres in diameter that may represent a unique habitat for bacteria in freshwaters. Bacteria inside the colony are segregated from the surrounding water and largely dependent on the metabolism of this primary producer. However, the existence of a specific bacterial community associated with free-living representatives of Nostoc from lakes and streams is unknown. Here, we studied large Nostoc spp. colonies (ca. 2-10 cm in diameter) from two adjacent, high altitude aquatic environments and assessed the diversity and community composition of the bacterial community associated with the inner gelatinous matrix. Further, we compared this community with that of the lake’s littoral zone where the colonies live or with the outer layer of the colony in samples collected from a stream. Alpha bacterial diversity in the inner gelatinous matrix of the colonies from both sites was lower than in the littoral zone or than in the outer layer. Significant differences in community composition were found between the inner and the outer layer, as well as between the inner gelatinous matrix and the littoral zone. Further, these differences were supported by the putative metabolic processes of the bacterial communities. Our results indicate the existence of a specific bacterial community inside macrocolonies of Nostoc spp. and also imply that the inner environment exerts a strong selection. Finally, these large colonies represent not only a unique habitat, but probably also a hotspot of bacterial activity in an otherwise oligotrophic environment.